Genetic variability in Bracco Italiano dog breed assessed by pedigree data - Francesca Cecchi (Italian Journal of Animal Science, 2013)
The Bracco Italiano is one of the oldest pointing dog breed, used for hunting ever since the Renaissance time. The complete electronic record of the breed was downloaded from the ENCI database [whole population (WP) = 24,613 animals registered since 1970 to 2011] with the aim to estimate genetic variability in Bracco Italiano dog breed using pedigree records. Up to 97% of the individuals had registered parents and 86% registered grand-fathers. Average generation interval was 4.68±0.545 for stallions and 4.08±0.321 year for dams. Reference population (RP) was defined as the population of interest that include living reproductive animals approaching the last three generations and include 9006 dogs of which 34% were inbreds. The number of ancestors was 564 in WP and 188 in RP, while the effective number of ancestors was 46 and 34 respectively. To explain 50% of the genetic variability, a total of 18 and 9 ancestors enough, respectively in the WP and RP. The average inbreeding coefficient in the RP resulted 6.7% while the average increase in inbreeding was estimated to be 1.29% (Ne=38.86). Nevertheless a regular monitoring of genetic variability of the population is important and must be adopted, in order to avoid the danger of an excessive increase of inbreeding in the future, which would result in significant inbreeding depression and in significant loss of genetic variation.